Perancangan Alat Press Body Motor Menggunakan Sistem Hidrolik - Anhar Khalid; Raihan Raihan; Akbar Ela Heka; Muhammad Kasim (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Nowadays industrial development in our country is also very fast along with the expansion of the kind of industrial products. The human role to control the device is still dominant, and will ultimately affect the outcomes as the work process is slowed down and will affect the efficiency and productivity of the industry, such as the advantages that the industrial work system offers. To facilitate the work, this tool can be useful for repairing motor vehicle bodies such as velg, front T-shock, frame, shock rod and press bearing. Therefore the author took the title Body Motor Press Tool Using Hydraulic System. Research is conducted using survey methods that are supported by searching for library references that are relevant to research as well as conducting flow planning and implementation processes. The hydraulic is assembled with an oil diffuser hose that is already mounted in the hydraulics valve and will be installed directly onto the hydrological socket that is above the press. The working system of this tool is used to compress the motor body. The power source used is from electric current.